THE EFFECT OF LIQUID SMOKE CONCENTRATION ON BARACCUDA FISH (Sphyraena jello) STICKS ON CONSUMER ACCEPTANCE - Monika Triana; N. Ira Sari; Tjipto Leksono (Berkala Perikanan Terubuk, 2020)
The aim of the research was to evaluate effect of soaking baraccuda fish stick into the liquid smoke at varied concentration on the consumer acceptance and to determine the optimum concentration of liquid smoke in the processing of smoked fish sticks. The treatment given was soaking the fish into the liquid smoke solution at varied concentration (0%, 4%, 8%, and 12%).  The parameters used to evaluate the product were sensory evaluation (appearance, aroma, texture and taste), water content, the content of total phenols, and total acids. The best product of smoked fish sticks was shown by the treatment of soaking the fish into the liquid smoke solution at the concentration of 8%.  It was indicated by the most number of panelist (95%) preferred to this product that characterized long flat appearance and a yellow-gold color (score 6.8), a distinctive smoky aroma suitable to the fish aroma (score 6.8), crunchy texture (score 6.8), and a distinctive taste of smoked fish (score 6.9). The product contained the water 1.68%, total phenols 12.8 ppm, and total acids 1.25%.